Interpersonal Communication Strategies of Program Facilitators in Implementing the Bestee Program at PT Bank BTPN Syariah Telanaipura - SELAMET RIADI; Yusnaini Yusnaini (Communication Studies Program Faculty of Social and Political Sciences Universitas Nurdin Hamzah Jambi, Indonesia, 2026)
This study aims to analyze the interpersonal communication strategies applied by supporting facilitators in the Bestee Program of PT Bank BTPN Syariah Telanaipura. The Bestee Program is an empowerment initiative designed to help productive underprivileged clients develop their business capacity and achieve economic independence. In this context, the facilitators play a vital role in building effective interpersonal relationships with clients to ensure optimal mentoring outcomes. This research employs a qualitative descriptive approach with data collected through interviews, observations, and documentation. The informants consist of three facilitators and five active clients selected using purposive sampling. The findings reveal that facilitators implement five main dimensions of interpersonal communication as proposed by Devito (2016): openness, empathy, positiveness, supportiveness, and equality. These dimensions serve as the foundation for establishing trustful and harmonious relationships between facilitators and clients. However, the study also identifies several psychological and technical barriers, such as limited communication experience and insufficient mentoring support. The study concludes that effective interpersonal communication strategies are essential in strengthening the empowerment process and promoting inclusive, socially oriented practices within Islamic banking institutions.